Lack of Commitment? Work Orientations of Finnish Employees in a European Comparison - Turunen, Teemu (Nordic Journal of Working Life Studies, 2014)
It has been argued that individuals’ employment commitment, that is, their commitment to work in general is crucial in today’s labor markets where life-long employment relationships are less frequently offered by organizations. In addition, employees’ organizational commitment, that is, their commitment to their own organization is also vital for organizations and firms, affecting many areas of importance to them. This article asks how Finnish employees rank in both employment commitment and affective organizational commitment compared with employees in 15 other European countries. The data were collected in 2005–2007 through the International Social Survey Program (ISSP), Work Orientation Module III. The results show Finnish employees scoring below European averages in both types of commitment when employee-level and organizationlevel factors are taken into account. Employment commitment was highest in Norway and affective organizational commitment highest in Portugal. The perceived intrinsic rewards of the job were the strongest predictor of employment and affective organizational commitment in most of the countries researched, increasing both these types of commitment. However, the perceived social relations between management and employees were found to be the most powerful determinant of affective organizational commitment in Finland, with perceived good relations adding to the affective organizational commitment of employees. The data were analyzed mainly by means of a general linear model procedure.